Datasets from harmonised metabolic phenotyping of root, tuber and banana crop - Drapal, Margit; Pérez Fons, Laura; Price, Elliott; Amah, Delphine; Bhattacharjee, Ranjana; Heider, Bettina; Rouard, Mathieu; Swennen, Rony L.; Becerra López Lavelle, Luis Augusto; Fraser, Paul (Elsevier, 2022)
Biochemical characterisation of germplasm collections and crop wild relatives (CWRs) facilitates the assessment of biological potential and the selection of breeding lines for crop improvement. Data from the biochemical characterisation of staple root, tuber and banana (RTB) crops, i.e. banana (Musa spp.), cassava (Manihot esculenta), potato (Solanum tuberosum), sweet potato (Ipomoea batatas) and yam (Dioscorea spp.), using a metabolomics approach is presented.